Stochastic optical solitons of the perturbed nonlinear Schrödinger equation with Kerr law via Ito calculus - Onder, Ismail; Esen, Handenur; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa; Qureshi, Sania (SPRINGER HEIDELBERG, 2023)
In this paper, we studied stochastic perturbed nonlinear Schr & ouml;dinger equation in fibers with Kerr law nonlinearity. The investigated model is important for the optical pulse propagation in fibers. In addition, we introduced the stochastic version of the related model. We have used the F-expansion method to obtain optical soliton solutions. As a result of the implementation, we reached dark, bright, periodic-singular and periodic soliton solutions. Besides all, we have investigated the white noise effect on the obtained results by simulating the graphics. Moreover, we discussed the effects of some parameters by presenting them in 2D views. The strength face of this study are introducing the stochastic model, obtaining its solutions, investigating noise and parameter effects for the first time.
Keywords: F-EXPANSION METHOD; PERIODIC-WAVE SOLUTIONS; Physics